Crystallization of the fusible component in Ag/Bi/Ag and Ag/Pb/Ag layered film systems - Dukarov, S.V.; Petrushenko, S.I.; Sukhov, V.N.; Sukhov, R.V. (Functional Materials, 2018)
The results of studies of the supercooling during the crystallization of a fusible component in Ag/Bi/Ag and Ag/Pb/Ag layered film systems are presented. The crystallization temperatures of metastable melts are determined by using two independent in situ techniques. The value of supercooling and the character of crystallization in Ag/Bi/Ag samples is determined by the condensation mechanism during the bismuth deposition (vapor-crystal or vapor-liquid). This phenomenon is explained by differences in the morphological structure of the films.